Contract of transferring technical assistance in the UAE space sector - Nada Zuher AL Feel (الرافدین للحقوق, 2019)
That the most important objectives pursued by the Emirates space agency to achieve; is the development of human cadres, and support their educational activities in space in addition to attracting national talent for the UAE space sector, and development of the uses of space science and technology, and found this study in the contracts for the transfer of assistance It is possible to transfer technical knowledge and expertise from the party that informs the supplier (the recipient), which are contracts of an international nature, that play a distinct role in putting the technical knowledge into practice and training the users M Has acquired the expertise and skills for its application in the production process, yet it has no independent legal organization.   The study discussed the concept of technical assistance, its contracts, legal nature and legal provisions within the UAE space sector, and reached the need for legislative intervention to organize technology transfer contracts, including the contract of transfer of technical assistance, with legal provisions that deal with all issues that may arise. Emirates Space Agency for technical assistance or supply, especially as the Emirates Space Agency plans to prepare a space law for the UAE to regulate the space sector in the country.